2014
DOI: 10.3389/fnint.2014.00029
|View full text |Cite
|
Sign up to set email alerts
|

CCL2-ethanol interactions and hippocampal synaptic protein expression in a transgenic mouse model

Abstract: Chronic exposure to ethanol produces a number of detrimental effects on behavior. Neuroadaptive changes in brain structure or function underlie these behavioral effects and may be transient or persistent in nature. Central to the functional changes are alterations in the biology of neuronal and glial cells of the brain. Recent data show that ethanol induces glial cells of the brain to produce elevated levels of neuroimmune factors including CCL2, a key innate immune chemokine. Depending on the conditions of et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…In agreement with research demonstrating that cytokines are increased in brain by stress (Madrigal et al 2010; Vecchiarelli et al 2016), substitution of the two initial withdrawals of the CIA protocol with intracerebroventricular (ICV) (1 week apart) of the chemokine (C-C motif) ligand (CCL2) before the final 5 days of the alcohol diet enhanced anxiety-like behavior during withdrawal from the single final 5-day alcohol exposure versus 5 days of ethanol diet (Breese et al 2008; Knapp et al 2011). In accord with this finding, elevation of CCL2 alone altered hippocampal synaptic function (Nelson et al 2011) and elevation of CCL2 in combination with alcohol altered hippocampal synaptic structure (Gruol et al 2014). CCL2 and CCR2 knockout mice were shown to have altered alcohol drinking behavior (Blednov et al 2005), a finding that further supports the idea that CCL2 influences neural function underlying behavior.…”
Section: Introductionmentioning
confidence: 55%
“…In agreement with research demonstrating that cytokines are increased in brain by stress (Madrigal et al 2010; Vecchiarelli et al 2016), substitution of the two initial withdrawals of the CIA protocol with intracerebroventricular (ICV) (1 week apart) of the chemokine (C-C motif) ligand (CCL2) before the final 5 days of the alcohol diet enhanced anxiety-like behavior during withdrawal from the single final 5-day alcohol exposure versus 5 days of ethanol diet (Breese et al 2008; Knapp et al 2011). In accord with this finding, elevation of CCL2 alone altered hippocampal synaptic function (Nelson et al 2011) and elevation of CCL2 in combination with alcohol altered hippocampal synaptic structure (Gruol et al 2014). CCL2 and CCR2 knockout mice were shown to have altered alcohol drinking behavior (Blednov et al 2005), a finding that further supports the idea that CCL2 influences neural function underlying behavior.…”
Section: Introductionmentioning
confidence: 55%
“…For example, high doses of CCL2 were most effective in studies using CCL2 infusion. Our ELISA studies of hippocampus and cerebellum indicate that tissue levels of CCL2 are considerably lower (~1.5 ng/ml) (Gruol et al, 2014) than the most effective doses of CCL2 (e.g., 2 μg/d) in the infusion experiments. Differences in the brain regions exposed to CCL2, and cellular accessibility may also be important differences between the two studies.…”
Section: Discussionmentioning
confidence: 76%
“…Further studies will be needed to test this possibility. There was no genotypic difference in the level of mGluR2/3 in the hippocampus from alcohol naïve CCL2-tg and non-tg mice (Gruol et al, 2014). …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Alcohol has also been shown to engage the immune pathway. Gruol et al ( 2014 ) used a transgenic mouse model overexpressing the immune cytokine CCL2 to determine if elevated levels of CCL2 interact with the effects of ethanol in the hippocampus and found that elevated levels of CCL2 protected against the effects of acute ethanol on synaptic plasticity (i.e., LTP).…”
mentioning
confidence: 99%